Avaliação dos serviços da Atenção Primária à saúde na Estratégia Saúde da Família de Sobral, Ceará. - Brito, Thalanikelson de Oliveira (2022)
Primary health care (PHC) is usually the first point of contact, offering comprehensive, accessible, community-based care that can meet 80% to 90% of a person's lifetime health needs. The objective of the study was to evaluate the attributes of Primary Health Care in the Family Health Strategy in the municipality of Sobral, Ceará. This is an evaluative research, of quantitative approach, with cross-sectional design, carried out in the period from October/2020 to June/2022. The place of study was the municipality of Sobral. The study population was composed of users of the Family Health Strategy. The sample consisted of 381 users of both genders, selected randomly, stratified and proportional to the coverage territory. The interviews were carried out in the FHC, using the Primary Care Assessment Tools PCATool-Brazil-2020 - Adult Version, composed with sociodemographic information and Likert-type questions to assess the PHC according to its attributes. SPSS 22.0 was used for statistical analysis of the data, using the Kruskal Wallis, Mann-Whitney and Chi-square tests, considering a 5% significance level. The attributes of PHC were calculated by means of the averages of the scores obtained and qualitatively in the categories: high and low referring to the evaluation of the service. The global scores were below the expected value (6.6), indicating low orientation towards the general, essential and derived attributes of Primary Health Care. It showed, however, high orientation in affiliation and in the utilization component. Only 22% (n=5) of units showed high orientation for the general global score, 30% (n=7) for the essential global score, and 9% (n=2) of units showed high orientation for the derived global score. Factors associated with this below average assessment were: Absence of support/attention in night periods, as well as Saturdays and Sundays; difficulties in external communication (outside the care) between user and team; weaknesses in the initiative of the referral, in the interest, in the search for information and results of the care of users in specialized services; hesitation to ask the ideas and opinions of users for the care strategies; as well as, facing the guidance, stimulus and invitation of users to participate in these spaces of social control. It is concluded that, from the users' assessment through the PCATool instrument, the Family Health Strategy in the municipality of Sobral presents low orientation regarding the attributes of Primary Health Care.